Photoresponsive supramolecular self-assemblies at the liquid/solid interface - Frath, Denis; Yokoyama, Soichi; Hirose, Takashi; Matsuda, Kenji (Journal of photochemistry and photobiology. C, Photochemistry reviews, 2018)
[Display omitted] •An overview of advances on photoresponsive supramolecular self-assemblies formed at the liquid/solid interface is given.•The photoresponsive assembly at the liquid/solid interface are compared with the systems under ultra-high vacuum or at air/solid interface.•The studies on molecular assemblies at the liquid/solid interface from a supramolecular chemistry perspective are also introduced.•Recent progress in the analysis of adsorption using the nucleation–elongation model for two-dimensional self-assembly will be featured and discussed. Control over molecular nanostructure is of the utmost importance in bottom-up strategies to create functionalized surfaces for electronic devices and advanced materials. In this context, the study of two-dimensional self-assembled structures consisting of organic molecules on surfaces using scanning tunneling microscopy (STM) has been the subject of intensive research. The formation of stimuli-responsive assemblies, especially photoresponsive ones, on surfaces is attracting interest. Meanwhile, assemblies formed at the liquid/solid interface have been extensively studied using STM from a supramolecular chemistry perspective in order to understand the assembly process of the molecules from the solution phase to the substrate interface. In this review, an overview of advances in photoresponsive supramolecular self-assemblies formed at the liquid/solid interface is given. Recent progress in the analysis of the adsorption process using the nucleation–elongation model of two-dimensional self-assembly will be featured and discussed in the context of photochemical control of the assembly.